Pathways toward inclusive low-emission dairy development in Tanzania: Producer heterogeneity and implications for intervention design - Kihoro, E.M.; Schoneveld, George C.; Crane, Todd A. (Elsevier, 2021)
Reducing greenhouse gas (GHG) emissions from the agriculture sector – especially livestock – through low-emission development (LED) has attracted increased global attention. However, producers rarely prioritize emission reduction in their day-to-day practices, resulting in a mismatch between global and national environmental policies and local development interests. This raises the urgency of identifying overlapping solution spaces that would address global and national environmental targets and farmers' production goals. The objective of this study is to identify pathways for scaling LED that better account for divergent smallholder capabilities, strategies, and interests. A multivariate cluster analysis was used to evaluate producer heterogeneity. The analysis utilized data from 1176 household surveys in Tanzania. Informed by these results, stakeholder workshops were held to identify how each group is uniquely constrained in the adoption of LED practices and viable paths forward. Our results reveal six distinct farmer types, distinguishable by their asset base, livestock ownership, cattle breeds, access to market, and income diversity. The six groups presented three levels of LED uptake, high, moderate, and low. Variants of technological packages and market-based interventions, access to better quality inputs, and extension services will be more impactful when correctly matched to producers' asset portfolios, interests, and needs for the high and moderately intensifying producers. However, interventions that address both the knowledge and resource gaps for producers who demonstrate low uptake of LED will be more appropriate. Achieving GHG reduction will be modest from already intensifying groups and the low uptake groups, while moderately intensifying groups present the highest leverage for increased GHG reduction potential. This highlights how taking a food system approach rather than a technological package would be more beneficial especially in targeting groups that are not interested in LED. This study challenges the conceptualization of LED as a simple technological fix. We demonstrate that LED, as currently conceptualized, is not equally accessible or appealing to everyone. Consequently, successful LED uptake is contingent on donor and state ability to match LED strategies, local development priorities, and food systems objectives to develop more targeted needs-driven implementation pathways.